PRACTICAL DEMONSTRATION OF THEORETICAL AND PRACTICAL CORRESPONDENCE OF TURKISH TULIP PATTERNS ON ZARDOZI CLOTHES - Ceyhun Berkol; Shakhrizoda Jakhonova (Bright Mind Publishing, 2025)
This thesis explores the integration of Turkish tulip motifs into traditional Uzbek zardozi embroidery. By examining both the theoretical symbolism of the tulip and its practical application in contemporary garment design, the study highlights a successful cultural fusion. Case studies from the “Malika Sultan” factory and designer Shakhrizoda Jakhonova illustrate how traditional motifs can be revived with elegance and meaning. The work underscores the ongoing relevance of heritage embroidery in modern textile arts.
Keywords: Turkish tulip, zardozi embroidery, Uzbek textile, gold thread, traditional motifs, cultural fusion, fashion design.